Impacts of workplace noise exposure and mitigation strategies: a scoping review - Lucas K. Kanu; Sophie Memory Kunda Lwara; Xiaojing Meng (Discover Public Health)
Abstract Occupational noise exposure is a major problem in many countries and workplaces, like industries, factories, mining areas, etcetera. Prolonged exposure to high levels of noise in the workplace can lead to a variety of adverse health effects, including noise-induced hearing loss (NIHL), cardiovascular diseases, stress, sleep disturbances, and decreased cognitive performance. This review aims to synthesize current research on the physiological and psychological impacts of occupational noise exposure, identify industries and occupations most at risk, and evaluate the effectiveness of existing noise control measures. The review involved searching relevant articles in PubMed, Web of Science, Scopus, and Science Direct databases. It begins with an overview of the physiological effects of noise exposure, highlighting the mechanisms by which noise induces hearing loss and other health issues. Studies show that noise levels between 75 and 85 decibels (dB) are particularly harmful, with risks increasing significantly with both the intensity and duration of exposure. The psychological impacts of noise, such as increased stress levels and reduced workplace productivity, are also examined, noting that these effects can further exacerbate the overall health burden on workers. The review identifies research gaps, including the need for more longitudinal studies to assess the long-term effects of low to moderate noise exposure and the efficacy of combined control measures. Future directions include the development of advanced noise monitoring technologies and the integration of noise control strategies into broader occupational health and safety frameworks.